Evaluation of Pseudomonas fluorescens for biocontrol of early blight (Alternaria solani) in tomato in North Wollo, Ethiopia - Birhan Berihun Abebe; Abebe Girma Demissie; Habtie Bassie Felatie; Aderajew Adgo Tesema; Baye Wodajo; Wondye Ayaliew Shiferaw; Sualih Gobeze Hailu (PLoS ONE, 2026)
Tomato (Solanum lycopersicum) is a widely used vegetable in Ethiopia, but its production is severely affected by late blight, early blight and bacterial wilt. This study aims to isolate Pseudomonas fluorescens as a bio-control agent against Alternaria solani. Biological control using Pseudomonas fluorescens offers a potential alternative to chemical fungicides. Rhizosphere soil and healthy tomato roots were sampled from three Kebeles in North Wollo, Ethiopia. P. fluorescens was isolated on Pseudomonas Isolation Agar, while A. solani isolated from infected leaves on Potato Dextrose Agar and confirmed pathogenic on tomato seedlings. Three isolates of P. fluorescens (Pfs12, Pfk13, Pfsa31) were screened in vitro using the dual culture method, and their efficacy was further tested in vivo under greenhouse conditions. Isolates Pfs12 and Pfk13 showed moderate effectiveness against the radial growth of A. solani, achieving percent growth inhibitions of 56.04% and 55.04%, respectively. The standard chemical treatment (mancozeb) resulted in a 54.84% growth inhibition. The control group (Pseudomonas fluorescens) also demonstrated a moderate growth inhibition of 57.65% against A. solani. Data were gathered regarding disease parameters. The day after transplanting, the percent disease index was significantly lower in all treated groups compared to the control (water). The isolate Pfsa31 achieved the lowest disease index of 24.733%, which was comparable to the standard chemical treatment at 28.467%. Both treatments were significantly different from the control (water) at 60.333%. The findings showed the bio-control potential of selected P. fluorescens isolates as effective and environmentally sustainable alternatives to synthetic fungicides for the management of early blight disease in tomato cultivation, emphasizing the importance of utilizing indigenous strains for optimal performance.